Fundamentos constitucionais da sujeição passiva tributária - Rego, Arthur Paiva Monteiro (2015)
This dissertation investigates the personal criteria of the rule tax incidence matrix from the Constitution. As preliminary aspects for theme development, philosophy of language concepts were brought forward to explain the construction of knowledge, and how to get to the crucial point of law, the rule of law. From an analytical and hermeneutical method, the structure of the rule of law was analyzed, using the lessons of Paulo de Barros Carvalho, with regard to the rule array of tax incidence, focusing on the legal relationship, precisely on personal criteria. Thus, a study was done on the tax liability, tax constitutional principles and of its relationship with personal criteria. Finally, we tried to show that there is a "constitutional recipient tribute" from the examination of the materiality of taxes put in the Constitution